Neglected tropical diseases in Yemen: a systematic review of epidemiology and public health challenges - Ahmed Alhothily, Ibrahim Ahmed; Dapari, Rahmat; Che Dom, Nazri (BioMed Central Ltd, 2025)
Background: Yemen has experienced a dramatic increase in neglected tropical diseases (NTDs) amidst ongoing conflict and humanitarian crises. This systematic review aims to consolidate and analyse the available literature on NTDs in Yemen, focusing on aetiology, geographic distribution, and associated risk factors. Methods: A comprehensive literature search was conducted across five international databases and one national database, resulting in 3,652 identified records. After screening and applying eligibility criteria, 230 articles were included in this review. Data extraction focused on publication year, study design, sample types, diagnostic methods, reported pathogens, and geographic distribution. The aetiology of reported NTDs was categorized into four groups: viruses, bacteria, protozoa, and helminths. Results: Viral NTDs were the most frequently reported, accounting for 39% of the articles, followed by bacterial (26%), helminthic (21%), and protozoal NTDs (15%). Dengue virus, hepatitis B and C viruses were the most prominent viral pathogens, while bacterial NTDs were primarily caused by Escherichia coli, cholera, and Salmonella. Schistosomiasis and ascariasis were the most reported helminth infections, whereas leishmaniasis and malaria were the leading protozoal NTDs. Geographically, over 69% of the reported studies focused on northern Yemen, with the highest concentrations in Sana’a, Al Hudaydah, and Taiz. The review identified multiple risk factors, including poor sanitation, inadequate water quality, and urbanization, exacerbating NTD prevalence. Conclusions: The findings highlight the significant burden and regional disparities of NTDs in Yemen, emphasizing the need for targeted interventions. Prioritizing improvements in sanitation, water quality, and vector control measures, alongside community engagement, is critical. Policymakers must allocate resources effectively to address the root causes of NTDs and strengthen Yemen’s healthcare infrastructure.